1996
DOI: 10.1071/sr9960909
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mineral ratios between disaggregated and original clay fractions in some South African soils as affected by amendments

Abstract: Conflicting information is available on the propensity different soil clays exhibit to dispersion. We therefore assessed the relative stability of the clay components of 12 soil samples, from various parts of South Africa, to predominantly physical disruption by a mild disruptive treatment [mechanical shaking for 5 min in distilled water (DW), and after the addition of phosphogypsum (PG; 2% by weight) and polyacrylamide (PAM; 0.04% by weight)]. The soils differed markedly in their physical and chemical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…However, physical crusting or sealing of soils (and hence infiltration) is a function of many more factors than the density of plants. Such factors include clay mineralogy (Bühmann et al 1996), hydrophobicity (Hillel 1998), silt content, very fine sand content and the dispersibility of the clay fraction (Agassi et al 1981;Mills et al 2006). The consequences for water infiltration can be extreme.…”
Section: Introductionmentioning
confidence: 99%
“…However, physical crusting or sealing of soils (and hence infiltration) is a function of many more factors than the density of plants. Such factors include clay mineralogy (Bühmann et al 1996), hydrophobicity (Hillel 1998), silt content, very fine sand content and the dispersibility of the clay fraction (Agassi et al 1981;Mills et al 2006). The consequences for water infiltration can be extreme.…”
Section: Introductionmentioning
confidence: 99%
“…Biihmann and co-workers used a set of II soils on which they investigated a variety of erosion-related aspects, i.e., a) differences in mineral associations between dispersed and total clay fractions (Biihmann, Rapp & Laker, 1996). The unexpected finding was that the 'quartz content in the dispersed clay fraction' was m~rkedly higher than that in the total clay fraction.…”
Section: Mineralogy In Relation To Soil Propertiesmentioning
confidence: 99%
“…It has been found that soils with high quartz contents in their clay fractions are found widespread in South Africa (Laker, 2004). In addition, soils with high quartz contents in their clay fractions are extremely prone to disaggregation, crusting and erosion (Bühmann et al, 1996) and also to sub-surface compaction (Moolman & Weber, 1978). This would then be an important factor at especially Sites 1 and 2.…”
Section: Compactibility Of the Soilsmentioning
confidence: 99%
“…Clay mineralogy plays an important role in determining the susceptibility of soil to disaggregation of aggregates, and thus also in its vulnerability to crusting and erosion (Stern, 1990;Bloem, 1992;Bühmann et al, 1996;Rapp, 1998). This would also be the case with vulnerability to compaction.…”
Section: Compactibility Of the Soilsmentioning
confidence: 99%
See 1 more Smart Citation